Review on Psoriasis Disease - Malpure, Prashant S; Kadam, Gayatri R; Chitte, Sakshi D; Kale, Gaurav S (Asian Journal of Pharmaceutical Research and Development, 2022)
Psoriasis is an autoimmune disease characterised by the proliferation of keratinocytes throughout time. On average, it affects 2-5 percent of the world's population. Psoriasis treatment remains difficult due to a variety of factors influencing treatment, including patient compliance and adherence to therapy, delicate patient profiles, psychological factors, and skin as a barrier to topical delivery. Pathophysiology, triggering factors, and clinical categorization were covered in the first section. Topical, oral, biological, parenteral therapy, phototherapy, and phytopharmaceuticals were all covered in the second section.